STUDI KOMPOSISI DAN POTENSI VEGETASI HUTAN PRODUKSI DI WILAYAH KPHP MODEL DAMPELAS TINOMBO DESA LEMBAH MUKTI KECAMATAN DAMPELAS KABUPATEN DONGGALA - Mohammad Nizar; Adam Malik; Abdul Wahid (Jurnal Warta Rimba, 2016)
Forests play an important role in supporting the survival of life of living creatures, especially human beings, forests do not only provide immediate benefits as a source of forest timber and non-timber forest but also provide indirect benefits as a regulator of water management, soil fertility, erosion control, and landslides. So the existence must be maintained through regulation functions of forests. Therefore, KPHP is an institution that is closely related to the setting function of the forest. Forest production in the region KPHP Dampelas – Tinombo as the territory of Lembah Mukti village that damage has an area of about 735 hectares, therefore, requires a basic data about the composition and the potential production forest in Lembah Mukti village of using planning, management of forests and development of plantation forests. The research was conducted for 3 months starting from June to September 2014, in a production forest in Lembah Mukti village. The aims of research to determined the composition and potential vegetation in forest production. This research uses purposive sampling line continue, with the number of observation plots as much as 30 plots with a size of 20 m x 20 m. Production forest composition Lembah Mukti village consists of 25 types of vegetation, at the level of the tree in the plot as many as 169 individuals from 20 types of vegetation, while poles as many as 102 individuals of 14 species and seedlings stage as many as 73 individuals from 10 types of vegetation. Volume tree in the plot observations as much as  164,13 m3 of 169 individuals, the type of  Tapi – tapi (Haplolobus cellebicus) has the most volume with 51,22 m3 and the volume level of the pole inside the plot observations as much as 15,71 m3 of 126 individuals, Jabon types (Anthocepalus cadamba) has the highest volume with 4,13 m3.Keywords : Composition studies, Potential vegetation, Forest production.